2019
DOI: 10.1177/2333794x19894799
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know About Prevalence and Management of Intoxicated Women During Labor and Delivery?

Abstract: Objective. To review the published literature on women who were intoxicated at delivery and outcomes for their infants. Methods. A systematic literature review was utilized to identify articles meeting our inclusion criteria. After screening using titles and abstracts, we identified 34 articles requiring full-text review. Each of these were reviewed by at least 2 of the authors. We identified 12 articles that met our inclusion criteria. Results. We identified case reports of 16 mothers who delivered with a blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The majority of people who may have met the diagnostic criteria for FASD die before they get a chance to be diagnosed. Deaths from stillbirth, sudden infant death syndrome and infectious illness are examples [103][104][105].…”
Section: Fetal Alcohol Spectrum Disorder and Mortalitymentioning
confidence: 99%
“…The majority of people who may have met the diagnostic criteria for FASD die before they get a chance to be diagnosed. Deaths from stillbirth, sudden infant death syndrome and infectious illness are examples [103][104][105].…”
Section: Fetal Alcohol Spectrum Disorder and Mortalitymentioning
confidence: 99%
“…Among women of child-bearing age, 53.6% used alcohol in the past month and 18.2% binge drank [ 4 ]. Because up to 50% of pregnancies are unplanned, many of these women will have children with prenatal alcohol exposure [ 5 ]. Upon confirmation of pregnancy, most women quit or reduce alcohol use but 10.2% continue to drink [ 4 ] and recent studies indicate that over 8% of pregnant women are drinking at the end of pregnancy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…We identified 12 studies reporting on 16 women who had a positive blood alcohol concentration at delivery and where it was also measured in their infant. 3 We felt that a positive blood alcohol concentration in the infant eliminated the possibility that they had consumed alcohol in the hospital after delivery. We found that women who are drinking at labor and delivery are rarely reported.…”
mentioning
confidence: 99%
“…We found that women who are drinking at labor and delivery are rarely reported. 3 We then estimated that in the United States every year 34,285 women (93 per day) are drinking on the day of delivery. 3 Thus drinking at the end of pregnancy or during labor is not rare.…”
mentioning
confidence: 99%
See 1 more Smart Citation